Pengaruh Edukasi Thaharoh (Bersuci) Terhadap Peningkatan Kesehatan Masyarakat Melalui Kegiatan Posyandu Di Desa Gapuk Tua - Pasaribu, Heka Afriannur (Universitas Aufa Royhan, 2022)
ABSTRACT In the life of Islam, the problem of taharah is a basic thing that every Muslim must know. Thaharah or purification has a close relationship with health. Because holiness is definitely clean, and cleanliness is the base of health. In Indonesia, the problem of thaharah is still not well known by the public, according to random sampling conducted on 56 respondents as many as 24 respondents (42.9%) still do not know about this thaharah. They only know cleanliness, even though clean is not necessarily holy, but if it is pure it must be clean. This study uses a descriptive design through posyandu activities carried out in the village of Gapuk Tua. Keywords: taharah, knowledge, society